The Bamboo City: Nature-Based Development Model for a Regenerative City Through Bamboo - Manjunath, Neelam (MAJ - Malaysia Architectural Journal, 2025)
“At COP27, Bamboo was declared as one of the top five solutions to mitigate global warming, by replacing traditional housing materials such as carbon and steel with Bamboo helps reduce carbon emissions caused by the global housing sector.” (Washington Post 2022) Cities, as engines of growth, consume substantial amounts of energy and emit greenhouse gases (GHGs) with the building sector contributing 40% of all global emissions (IEA 2019). The adverse effects of an unsustainable built environment have put a strain on the environment, affecting humanity. In this scenario, Bamboo stands as an ideal nature-based solution capable of achieving soil and moisture conservation, providing water security, preventing soil erosion, repairing degraded lands, improving air quality, and providing eco-friendly buildings because of its manifold uses and industrial applications rendered possible by recent advancements. The 2030 Climate and Energy Framework states that 27% of energy should be sourced from sustainable energy sources to meet the target for 2030. (EU 2021). This paper is part of her C40 Women4Climate project by the author. It examines the current state of environmental impacts of air and water pollution in cities like Bangalore and intercedes through nature-based interventions with Bamboo as a mainstream material in construction, phytoremediation, and air pollution mitigation by collating available data, engaging with stakeholders, and identifying points of action consistent with national and international climate action and sustainability commitments among governments. The Bamboo City project will be a plug-in to the main Climate Action Plan with a roadmap for lowering GHG emissions and building community climate resilience to achieve carbon neutrality by 2030 and regenerative status thereafter. Using Bamboo for sustainable development in the city will not only cut greenhouse gas emissions but also provide income opportunities, ensuring the triple bottom line of environmental, economic, and social growth thus fulfilling the SDGs.